2015
DOI: 10.1155/2015/195469
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Events among Children and Adolescents with Sickle Cell Disease in Basra, Iraq

Abstract: Objectives. Despite improvements in the management of sickle cell disease (SCD), many patients still experience disease-related complications requiring hospitalizations. The objectives of this study were to identify causes of hospitalization among these patients and factors associated with the length of hospital stay (LOS) and readmission. Methods. Data from 160 patients (<14 years old) with SCD who were admitted to the Basra Maternity and Children's Hospital from the first of January 2012 through July 2012 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 28 publications
(35 reference statements)
9
14
1
Order By: Relevance
“…On the other hand, the results that are presented in clearly prove this fact that one of the main symptoms that patients presented at the last admission was epigastric pain and dyspepsia with 33.3% followed by abdominal pain with 26.2%. This results are similar to those of the studies carried out by Jesse et al [49] and Donze et al [35] who showed that abdominal and epigastric pain are the most common presentations among patients who may be readmitted to hospitals. In accordance with the information presented in Table (3), it could be seen that just one of the patients had a long hospitalization period of 36 days, and more than 50% of them stayed in hospital less than 5 days.…”
Section: Incidence Of Readmission In Patients In Sulaimani Emergency supporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the results that are presented in clearly prove this fact that one of the main symptoms that patients presented at the last admission was epigastric pain and dyspepsia with 33.3% followed by abdominal pain with 26.2%. This results are similar to those of the studies carried out by Jesse et al [49] and Donze et al [35] who showed that abdominal and epigastric pain are the most common presentations among patients who may be readmitted to hospitals. In accordance with the information presented in Table (3), it could be seen that just one of the patients had a long hospitalization period of 36 days, and more than 50% of them stayed in hospital less than 5 days.…”
Section: Incidence Of Readmission In Patients In Sulaimani Emergency supporting
confidence: 92%
“…In another study in the USA, the readmission rate among trauma patients was 1.7 [47]. Kociol et al (2012) reported that readmission rates in the USA and non-US countries are respectively 10.5 and 7.7% [49]. A study carried out in Basra, Iraq indicated that readmission rate was 23.1% among children and adolescents with sickle cell disease [50].…”
Section: Discussionmentioning
confidence: 98%
“…Vasocclusive crisis outnumbered all other described crisis in this patient population, while going back to a study published in 1982 the most common cause of death was attributed to acute chest syndrome in a study conducted at Jamaica as well as by authors J. Brambilla et al in their study published in the new England journal. 6 Vasoocclusive crisis is also the most common cause leading to mortality in this study group claiming 41% as cause of death which can also be seen in a study conducted in basra by authors Zeina et al 9 Authors such as Acharya et al have also noted correlation of sickle cell nephropathy to ophthalmic manifestations in patients, and other unusual presentations such as renal tubular acidosis with hyperkalemia. 10,11 Specific lab parameters such as Mean Platelet Volume and other platelet indices have been found useful to estimate frequency of crises in such patients as well.…”
Section: Discussionsupporting
confidence: 76%
“…Among the 217 hospitalized SCD children, 77.9% received blood transfusion therapy as part of their in-patient management care. Transfusion frequency in our sample is comparable to those reported by others, 80.6% from Congo [16] and 73.8% from Iraq [17]. However, our frequency rates were higher than the 31.0% reported from Oman [18] and 39.1% in Nigeria [19] but lower than 90.3% reported in a Tanzanian study [20].…”
Section: Discussionsupporting
confidence: 76%